Pembrolizumab Plus Chemotherapy Versus Chemotherapy Monotherapy as a First-Line Treatment in Elderly Patients (≥75 Years Old) With Non-Small-Cell Lung Cancer - Yang, Zhengyu; Chen, Ya; Wang, Yanan; Hu, Minjuan; Qian, Fangfei; Zhang, Yanwei; Zhang, Bo; Zhang, Wei; Han, Baohui (Frontiers in Immunology, 2022)
Objective Several trials have shown that pembrolizumab plus chemotherapy was more effective in patients with advanced non-small-cell lung cancer (NSCLC) than chemotherapy monotherapy. However, whether pembrolizumab plus chemotherapy is still a better choice for first-line treatment in elderly patients (≥75 years old) remain unknown. We retrospectively compared the efficacy and safety of these two treatments in elderly patients. Patients and Methods We collected data of 136 elderly patients with advanced NSCLC who were treated with pembrolizumab plus chemotherapy or chemotherapy monotherapy in our hospital from 2018 to 2020. We compared the progression-free survival (PFS) and overall survival (OS) of patients and analyzed which subgroups might benefit more significantly from pembrolizumab plus chemotherapy. Results In total population, pembrolizumab plus chemotherapy showed superior PFS and OS than chemotherapy monotherapy (PFS: 12.50 months vs. 5.30 months, P<0.001; OS: unreached vs. 21.27 months, P=0.037). Subgroup analysis showed patients with positive PD-L1 expression, stage IV, good performance score (ECOG-PS <2), fewer comorbidities (simplified comorbidity score <9) or female patients had demonstrated a more evident OS benefit in pembrolizumab plus chemotherapy. In terms of safety, the pembrolizumab plus chemotherapy group had higher treatment discontinuation (26% vs. 5%). Conclusions Elderly patients using pembrolizumab plus chemotherapy achieved longer PFS and OS, but were more likely to discontinue due to adverse effects, so disease stage, PD-L1 expression, ECOG-PS and comorbidities should be considered when selecting first-line treatment.